Preparation of nanosilica powder using rice husk via precipitation method - Mohd Daud, Farah Diana; M.Azmy, Nur Aishah; Mahmud, Mudrikah Sofia; Sarifuddin, Norshahida; Mohd Zaki, Hafizah Hanim (Trans Tech Publications Ltd, 2020)
Silica in nanoscale has various superior properties which leads to a wide range of applications. Most researches used and metal alkoxides as the sources but very few researches attempted at preparing nanosilica powder from the agricultural waste which environmental friendly and inexpensive. This research is presented as the studies of optimization of parameters involved during preparation, aimed to improve the purity of silica produced. In this work, rice husk ash (RHA) precursor was subjected to precipitation method in order to produce nanosilica powder. Acid leaching and thermal treatment were done as a pre-synthesis process. The process parameters that have been studied were the reuxed NaOH concentration, heating time, and temperature, in which the properties were then evaluated during characterization process. The results from X-Ray Flourescence (XRF) conrmed that it is possible to extract 100% purity of silica from RHA treated by the combination of thermal treatment, acid leaching, reuxed with 2.5 M of NaOH and heated at 50°C for 48 hours. X-Ray Diraction (XRD) illustrated that the produced silica is in amorphous state. Meanwhile, the mean particle size of the spherical shape of silica obtained ranging from 44.7 nm to 1.23 μm. Therefore, the best mean particle size obtained was by using the sample reuxed with 2.5 M NaOH and heated at 50°C for 48 hours, which were conrmed by Scanning Electron Microscope (SEM) and Field Emission Scanning Electron Microscope (FESEM). These ndings on the optimum parameters indicate the successful production of highest purity of nanosilica powder with nanoscaled particle size.